Reading comprehension strategies:the use of prior knowledge as a cognitive strategy by grade 6 learners in a primary school in the Lephalale area - Lekota, K.B. (University of Limpopo, 2014)
Research shows that successful readers make use of prior knowledge. This is supported by schemata theory (Herczog & Porter, 2012; Xigo-hui, Jun & Wei-hua, 2007; Zhang 1993). In this study, the researcher intended to increase the schema of the selected sample and test the theorem. Two groups were selected as samples comprising an experimental group and a control group. The experimental group had the advantage of being exposed to a topic over a month and on the day of the test the two groups were combined and the results from the test were analysed. The outcomes showed that the experimental group out-performed the control group proving that prior knowledge increases chances of comprehension. In the initial test both groups had performed poorly. Many learners in the experimental group would have performed better if they could comprehend the English language. The students who used their schema on the experimental group did better than those who did not.
Thesis ( M.A. (English Studies) --University of Limpopo, 2014
Keywords: Comprehension strategies; Prior knowledge; Cognitive strategy; Primary school learners; 372.10968; Learning ability; Education,Elementary --South Africa